STUDENTS’ SOCIAL ACTIVITIES, VALUES, MEANINGFULNESS OF LIFE AND SELF-CONFIDENCE - Ļevina, Jeļena; Mārtinsone, Kristīne; Mihailova, Sandra; Sokola-Nazarenko, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The purpose of this study was to develop and test a model that describes the relations between participation of students in social activities oriented toward helping others, their values, namely, discrepancy between importance and attainability of values, meaningfulness of life and self-confidence. The sample consisted of 103 students aged from 18 to 41, 28.2% were males and 71.8% were females. In this research the M.Rokeach technique as modified by E.B. Fantalova, the Meaning-in-Life Orientations test (MOL) developed by D.A. Leontiev, the Self-confidence scale of the “Research of self-attitude” questionnaire (RS) developed by V.V.Stolin and S.R. Pantelejew, and questions from the third European Quality of Life Survey, which measure participation in social activities oriented towards helping others, were used. The first three instruments were translated into Latvian by S. Jirgena (now Mihailova). Validity and reliability of the Latvian versions of the MOL and the RS Self-confidence scale were evaluated, and the Latvian versions of both scales were modified. Correlation analysis and structural equation modeling (SEM) were used in order to test a theoretically developed model of students’ participation in social activities oriented towards helping others/ discrepancy between importance and attainability of values and meaningfulness of life outcome, and meaningfulness of life and self-confidence outcome. Firstly, it was found that discrepancy between importance and attainability of students’ values is not related to meaningfulness of life. In its turn, it was revealed that participation in such social activity as doing unpaid voluntary work in education, cultural and professional associations has a positive impact on meaningfulness of life and, in its turn, meaningfulness of life has a positive impact on self-confidence.